2021
DOI: 10.1002/adfm.202109076
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hierarchical Structures for Contact‐Sensible Adhesives

Abstract: Bioinspired structural adhesives that are capable of bonding two objects together have recently found widespread applications in industrial fields, because of their promising reusability and environmental friendliness. However, such adhesives are usually monofunctional and cannot yield real‐time detection on the adhesion status, which is important for both biological systems (e.g., Gecko) and engineered mimics. This study reports a new hierarchical structure with the monolithic integration of adhesion and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…This ultrahigh sensitivity over a broad pressure range is at least three orders of magnitude higher than that of existing capacitive sensors with bonded interfaces (Fig. 3B) (24)(25)(26)(27)(28)(29), allowing the sensor to be used for the monitoring of weak physiological signal such as fingertip pulse (fig. S11).…”
Section: Sensing Properties Of the Iontronic Skinmentioning
confidence: 90%
See 1 more Smart Citation
“…This ultrahigh sensitivity over a broad pressure range is at least three orders of magnitude higher than that of existing capacitive sensors with bonded interfaces (Fig. 3B) (24)(25)(26)(27)(28)(29), allowing the sensor to be used for the monitoring of weak physiological signal such as fingertip pulse (fig. S11).…”
Section: Sensing Properties Of the Iontronic Skinmentioning
confidence: 90%
“…Our iontronic skin is promising in robotic haptics and other applications because of its combined high performances. Whereas traditional designs for flexible pressure sensors can hardly achieve both high sensitivity and high mechanical robustness ( 24 , 26 , 27 , 38 41 ), our design of using embedded IMIGs enables combined high sensitivity (>174 kPa −1 in 0.15 Pa to 440 kPa) and high mechanical robustness (fracture limit: 289 N m −1 and interfacial toughness: 386 J m −2 ), in addition to skin-like softness and high stretchability (elongation at break >150%). In addition, our iontronic skin is made with a large area and high sensor density (28 × 28 pixels or ~8 pixels cm −2 ), close to the density of the mechanoreceptors in the human skin of the trunk.…”
Section: Discussionmentioning
confidence: 99%
“…A gecko’s toe pads have millions of setae, and this compliant fibrous structure enhances its adhesion to various surfaces. , The adhesion of individual fibers has been measured, demonstrating that van der Waals forces play a major role in the gecko’s adhesion ability. , Inspired by this unique structure, microfibrillar adhesives with various dimensions of structure elements and geometry have been developed. del Campe et al systematically compared the adhesion of PDMS microfibrillars of different size and tip shape, and found that shape exerts a stronger effect on adhesion than size. , Mushroom-shaped micropillars, a wedge-structured surface, funnel-shaped micropillars, , slanted functional gradient micropillars, , T-shaped gradient micropillars, , etc., were then fabricated for the purpose of achieving desirable dry reversible adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible pressure sensors hold wide application on healthcare monitoring [1][2][3][4][5] , electronic skin for robots [6][7][8][9] , and wearable electronics [10][11][12][13] due to their highly mechanical conformability and softness attributes to human body. Specially, exible iontronic pressure sensors (FIPS) have attracted much attention.…”
Section: Introductionmentioning
confidence: 99%